Insights into the photoluminescence properties of gel-like carbon quantum dots embedded in poly(methyl methacrylate) polymer. (March 2019) - Rodrigues, Joana; Pereira, Sónia O.; Soreto Teixeira, S.; Zhou, Yiqun; Peng, Zhili; Liyanage, Piumi Y.; Leblanc, Roger M.; Barros-Timmons, Ana M.M.V.; Costa, Luis C.; Costa, Florinda M.; Monteiro, Teresa
Graphical abstract: Highlights: Spectroscopic analysis of carbon dots embedded in poly(methyl methacrylate) (CDs/PMMA) with different CDs' loads. CDs/PMMA composites with strong blue and green emission depending on the used excitation density. Composites preferentially populated through two main excitation bands partially overlapped. Overlapping of emitting centres, which can be due to small fluorescent molecules at the CDs' surface. Abstract: Carbon dots (CDs) have become one of the most investigated nanomaterials in the last few years, since they offer excellent prospects to be used in a wide range of technological applications. Nonetheless, the understanding of the photoluminescence (PL) processes remains unclear and solely based on spectroscopic measurements at room temperature, which hampered a full discussion on the nature of recombination mechanisms. Insights into the CDs' PL and corresponding recombination models can be achieved from temperature, excitation energy and excitation density dependency studies. Thus, in this paper, CDs with a mean diameter of ∼3.0 nm were embedded in poly(methyl methacrylate) (PMMA) and studied by such optical techniques. The recombination of CDs/PMMA composites was found to be due to an overlap of emitting centres, both in the blue and green regions, with intensity and peak position strongly dependent on the excitation density. Moreover, this emission was found to be preferentially populated by two overlapped excitation bands. Temperature-dependent PL measurements corroborate the hypothesis of overlapped emitting optical centres (e.g. small molecules at the CDs' surface), as no shift on peak position and no changes in spectral shape were observed, which allow to exclude the hypothesis of a conventional free excitonic transition and quantum confinement effects, as observed in typical nanosized semiconductors with dimensions lower than the exciton Bohr radius.